Innovation and Competitiveness in the Territorial Brand of the Algarve: A Comparative Analysis of Its Social Media Communication and Web Content - Cristófol, Francisco Javier; Berraquero-Rodríguez, Diego; Zamarreño-Aramendia, Gorka; Falcão Alves, Paulo (Tourism and Hospitality, 2026)
In an increasingly competitive global tourism context, territorial branding plays a key role in enhancing the visibility, identity, and resilience of regions. This study focuses on the Algarve, a region in southern Portugal, and investigates how innovation and competitiveness are reflected in its digital communication strategy. Using a mixed-methods approach, this research combines the quantitative analysis of 689 social media posts published in 2024 on Facebook, Instagram, and YouTube with the qualitative content analysis of 38 documents and the official website of Algarve. The findings reveal a coherent and visually appealing brand narrative centred on the coastal identity of the Algarve, complemented by content related to nature, gastronomy, and cultural heritage. Instagram stands out as the most engaging platform, particularly when posts adopt a participatory tone, emotional storytelling, and references to specific locations. However, only 6.4% of the content surpassed the 1% engagement threshold, suggesting limited audience connection. The website presents a broader thematic range but under-represents intangible heritage and local products.The Algarve brand successfully projects an aspirational image based on landscape and leisure but would benefit from greater content diversification, enhanced stakeholder integration, and expanded narrative strategies to strengthen digital engagement and destination competitiveness.
Keywords: place branding; Algarve; social media; digital marketing; tourism competitiveness; place identity